2005
DOI: 10.1093/humrep/dei037
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of mifepristone in combination with misoprostol administered sublingually or vaginally for medical abortion at 13–20 weeks gestation

Abstract: Sublingual administration of misoprostol following mifepristone is an acceptable and effective alternative to vaginal administration for medical abortion at 13-20 weeks gestation. However, women should be advised about the greater likelihood of requiring stronger analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 23 publications
3
37
3
Order By: Relevance
“…There is a gradual increase in second-trimester abortion because of wide scale introduction of prenatal screening programs detecting women whose pregnancies are complicated by serious fetal abnormalities such as cardiovascular and skeletal malformation [2]. The most efficacious regimen for medical second trimester termination of pregnancy appears to be the use of a combination of mifepristone, followed by misoprostol [3][4][5]. This regimen has had 97-99% rate of abortion within 24 hours [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a gradual increase in second-trimester abortion because of wide scale introduction of prenatal screening programs detecting women whose pregnancies are complicated by serious fetal abnormalities such as cardiovascular and skeletal malformation [2]. The most efficacious regimen for medical second trimester termination of pregnancy appears to be the use of a combination of mifepristone, followed by misoprostol [3][4][5]. This regimen has had 97-99% rate of abortion within 24 hours [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The most efficacious regimen for medical second trimester termination of pregnancy appears to be the use of a combination of mifepristone, followed by misoprostol [3][4][5]. This regimen has had 97-99% rate of abortion within 24 hours [3,6]. In countries where mifepristone is not available or affordable, gemeprost or misoprostol alone have been shown to be effective, although a higher total dose is needed and is less effective than the combined regimens [7].…”
Section: Introductionmentioning
confidence: 99%
“…(3,8,9) Treatment with mifepristone softenes the cervix, increases sensitivity of uterus to prostaglandins. The maximum effect on uterine contractility and cervical ripening is seen after 36-48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Aggarwal N et al (10), 2.5% of patients aborted with mifepristone alone whereas other studies have reported 0.2% -0.5% incidence of complete abortion with only mifepristone. (5,8,14) There were seven patients in our study who had undergone caesarean section prior to present pregnancy. All of them had complete abortion with combination of mifepristone and Misoprostol regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation